A genomewide association mapping study using ultrasound‐scanned information identifies potential genomic regions and candidate genes affecting carcass traits in Nellore cattle. (27th May 2015) - Santana, M.H.A.; Ventura, R.V.; Utsunomiya, Y.T.; Neves, H.H.R.; Alexandre, P.A.; Oliveira Junior, G.A.; Gomes, R.C.; Bonin, M.N.; Coutinho, L.L.; Garcia, J.F.; Silva, S.L.; Fukumasu, H.; et al.
Summary: The aim of this study was to identify candidate genes and genomic regions associated with ultrasound‐derived measurements of the rib‐eye area (REA), backfat thickness (BFT) and rumpfat thickness (RFT) in Nellore cattle. Data from 640 Nellore steers and young bulls with genotypes for 290 863 single nucleotide polymorphisms (SNPs) were used for genomewide association mapping. Significant SNP associations were explored to find possible candidate genes related to physiological processes. Several of the significant markers detected were mapped onto functional candidate genes including ARFGAP3, CLSTN2 and DPYD for REA; OSBPL3 and SUDS3 for BFT; and RARRES1 and VEPH1 for RFT. The physiological pathway related to lipid metabolism ( CLSTN2, OSBPL3, RARRES1 and VEPH1 ) was identified. The significant markers within previously reported QTLs reinforce the importance of the genomic regions, and the other loci offer candidate genes that have not been related to carcass traits in previous investigations.